2005
DOI: 10.1086/427063
|View full text |Cite
|
Sign up to set email alerts
|

UVCS Observation of Sungrazer C/2001 C2: Possible Comet Fragmentation and Plasma‐Dust Interactions

Abstract: In this paper we analyze SOHO Ultraviolet Coronagraph Spectrometer (UVCS) observations of the sungrazing comet C/2001 C2, a member of the Kreutz family, observed on 2001 February 7 at heliocentric distances of 4.98 and 3.60 R . This comet apparently went through sequential fragmentation events along its path: further indication of fragmentation processes is provided by UVCS observations, which show the presence of two separate tails in the 4.98 R data set, which we interpret as two fragments unresolved by LASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
1
28
0
1
Order By: Relevance
“…Most sporadic near-Sun comets are likely to follow the trends observed in the general comet population, if they have a cometary origin. Kreutz comet nucleus sizes, however, have been estimated to be meters to tens of meters in radius by a variety of modeling and observational techniques, e.g., MacQueen and St. Cyr (1991), Raymond et al (1998), Uzzo et al (2001), Iseli et al (2002), Sekanina (2003), Bemporad et al (2005), Knight et al (2010). These sizes are similar to inferred from high resolution imaging with Hubble Space Telescope and/or thermal IR imaging with Spitzer Space Telescope, such as the 25-60 m range inferred for the fragments of split comets D/1999 S4 LINEAR (Weaver et al 2001); the tens of m estimated for 73P/Schwassmann-Wachmann 3-C (Weaver et al 2006;Reach et al 2009), and the inferred 9-30 m range for 332P/IkeyaMurakami (Jewitt et al 2016).…”
Section: Sizesmentioning
confidence: 99%
“…Most sporadic near-Sun comets are likely to follow the trends observed in the general comet population, if they have a cometary origin. Kreutz comet nucleus sizes, however, have been estimated to be meters to tens of meters in radius by a variety of modeling and observational techniques, e.g., MacQueen and St. Cyr (1991), Raymond et al (1998), Uzzo et al (2001), Iseli et al (2002), Sekanina (2003), Bemporad et al (2005), Knight et al (2010). These sizes are similar to inferred from high resolution imaging with Hubble Space Telescope and/or thermal IR imaging with Spitzer Space Telescope, such as the 25-60 m range inferred for the fragments of split comets D/1999 S4 LINEAR (Weaver et al 2001); the tens of m estimated for 73P/Schwassmann-Wachmann 3-C (Weaver et al 2006;Reach et al 2009), and the inferred 9-30 m range for 332P/IkeyaMurakami (Jewitt et al 2016).…”
Section: Sizesmentioning
confidence: 99%
“…Although it is clear they do not survive their perihelion, the actual distance at and process through which their nucleus is disrupted remain unresolved. Most of the sungrazers dim below detection at around 7 R s and may be completely destroyed by 3 R s , as a handful of UVCS observations suggest (e.g., Bemborad et al 2005). Furthermore, Kimura et al (2002) have suggested that sungrazers should exhibit a second brightness peak at 4-6 R s due to the sublimation of crystalline and amorphous pyroxenes.…”
Section: Science Question 9: 'What Is the Nature Of Dust-plasma Intermentioning
confidence: 99%
“…They imply nucleus sizes on the order of 10 m (Raymond et al 1998;Uzzo et al 2001;Bemporad et al 2005) to hundreds of meters (McCauley et al 2013). Increases in the apparent size of the nucleus imply breakup, providing an estimate of the tensile strength of the nucleus (Uzzo et al 2001).…”
Section: Introductionmentioning
confidence: 99%